STRUKTUR KOMUNITAS MOLUSKA DI PADANG LAMUN PERAIRAN PULAU BELITUNG PROVINSI BANGKA BELITUNG - Hendrik A. W. Cappenberg; Diah Anggraini Wulandari (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
The Belitung Island consists of small islands with seagrass area, which inhabited by species of mollusks but the diversity of in mollusk in these waters no yet widely known. Observations in Kelayang Island (BLTS01 station), Kepayang Island (BLTS02 station), Mendanau Island (BLTS03 station), Sekutai Island (BLTS04 station), Sebongkok Island (BLTS05 station), Ruk Island (BLTS06 station) and Kalimambang Island (BLTS07 station) was conducted on 29 August to 9 September 2018 to find out community structure and mollusks density. The method used was quadrant transect, starting from the edge of the beach perpendicular to the coast. From the results of the study, it was found 22 species of mollusk consisting of 10 species of bivalves class and 12 species of gastropods class. Anadara antiquata, Pinna bicolor and Gafrarium pectinatum from the bivalves class, and Lambis lambis and Strombus urceus from the gastropods class were having a relatively wide distribution. The highest mollusk density was found in station BLTS06 (23.283 individu/ha) and the lowest was in Station BLTS03 (283 individu/ha), respectively Isognomon isognomum was a species that dominated the sand substrate in BLTS06. The value of species diversity index (H') ranged from 2.42 to 3.52. This value indicated the diversity of mollusk species was of moderate condition. Evenness index (J') ranged from 0.71 to 0.86. From the results of this study, it can be concluded that the mollusk community in these waters is still in reasonably good condition.